The susceptibility of Mycobacterium tuberculosis to isoniazid and the Arg-->Leu mutation at codon 463 of katG are not associated. - Van Doorn, H; Kuijper, E; van der Ende, A; Welten, A; van Soolingen, D; de Haas, P; Dankert, J (2001)
A mutation (CCG-->CTG [Arg-->Leu]) in codon 463 of katG (catalase peroxidase) of Mycobacterium tuberculosis has been found in isoniazid (INH)-resistant strains. A PCR restriction endonuclease analysis to detect this mutation was applied to 395 M. tuberculosis isolates from patients in The Netherlands. The proportion of isolates with a detectable mutation was 32% (32 out of 100) and 29% (85 out of 295) among INH-susceptible isolates and INH-resistant or -intermediate isolates, respectively. Sequencing of five INH-susceptible isolates with such mutations showed that all five had the Arg463Leu mutation. We conclude that the Arg463Leu mutation of katG of M. tuberculosis is not a reliable indicator of INH resistance.